Involvement of a cryptic ATPase activity of UvrB and its proteolysis product, UvrB* in DNA repair - Caron, Paul R. (1988)
The incision of damaged DNA by the Escherichia coli UvrABC endonuclease requires ATP hydrolysis. Although the deduced sequence of the UvrB protein suggests a putative ATP binding site, no nucleoside triphosphatase activity is demonstrable with the purified UvrB protein. The UvrB protein is specifically proteolyzed in E. coli cell extracts to yield a 70 kD fragment, referred to as UvrB*, which has been purified and is shown to possess a single-strand DNA dependent ATPase activity. Substrate specificity and kinetic analyses of UvrB* catalyzed nucleotide hydrolysis indicate that the stimulation in DNA dependent ATPase activity following formation of the UvrAB complex results from the activation of the normally sequestered UvrB associated ATPase. Using nucleotide analogues, it can be shown that this activity is essential to the DNA incision reaction carried out by the UvrABC complex.